Labeling accuracy and detection of DNA sequences originating from GMOs in meat products commercially available in Greece. (February 2021) - Grammenos, Alexandros; Paramithiotis, Spiros; Drosinos, Eleftherios H.; Trafialek, Joanna
Abstract: The aim of the present study was to assess labeling accuracy and detect food fraud practices as well as to detect DNA sequences originating from GMOs in meat products commercially available in Athens, Greece. A total of 139 different samples from 23 producers were included in the study. DNA was extracted from the samples and subjected to PCR aiming for species-specific sequences for the detection of pork, beef, chicken, turkey, donkey and horse meat as well as the screening elements P–35S, T- nos, CP4- epsps, pat and bar, for the detection of DNA originating from GMOs. In total, 72 products, i.e. 52% of the samples, were mislabeled and correct labeling was verified for the products originating from only 7 out of the 23 companies. This mislabeling may be attributed to lack of good manufacturing practices that resulted in cross-contamination in 31 cases, definite substitution in 3 cases and suspected substitutions in 37 cases. Donkey and horse meat as well as DNA sequences originating from GMOs were not detected. Highlights: Correct labeling was verified for the products of 7 out of the 23 companies. 52% of the products assessed were mislabeled. Mislabeling can be principally attributed to lack of good manufacturing practices. Meat substitution was detected in three products. Absence of donkey and horse meat as well as DNA sequences originating from GMOs.